BRAINLIEST ANSWER FAST!Subtract and simplify. Show work to earn full credit.
1 answer:
Answer:
<h2>7y² - 6y -17</h2>
Step-by-step explanation:
(-2y^2-11y-7)-(-9y^2-5y+10) (firstly, we remove the brackets)
-2y^2 - 11y - 7 + 9y^2 + 5y - 10
= (-2y^2 + 9y^2) + (-11y + 5y) + (-7 - 10)
= (7y²) + (-6y) + (-17)
You might be interested in
7 dimes+7 pennies
or 77 pennies
or 7 dimes+1 nickle+2 pennies
<u>3 different ways!!!</u>
Answer:
13.
Step-by-step explanation: divide 15 and 10 to get 1.5 and then multiply 1.5 by 9
Answer: 0.33 seconds
Step-by-step explanation:
If xy=0
assume that at least x or y=0
3(x-3)=0
therefor
3=0 or x-3=0
3=0 is false
therefor
x-3 mus equal zero
x-3=0
add 3 to both sides
x=3
Answer:
24 cats: 28 dogs
Step-by-step explanation:
28/21 = 1.33
18 x 1.33 = 24